Investigation of education value perception scale's psychometric properties according to CTT and IRT - Harun Dilek; Ufuk Akbaş (International Journal of Assessment Tools in Education)
The purpose of this study is to develop Education Value Perception Scale (EVPS) based on Bronfenbrenner's Ecological Theory and to investigate its psychometric properties according to Classical Test Theory (CTT) and Item Response Theory (IRT). The data were collected from 2872 secondary school students by stratified purposeful sampling method. Measurement invariance of EVPS was tested by multigroup confirmatory factor analysis based on gender, and scalar invariance was observed to have been provided. The estimations based on IRT were conducted based on Graded Response Model. While high positive correlations were found between the item discriminations estimated according to different test theories, high negative correlations were identified between item means. McDonald’s Omega was calculated to be .79 according to CTT from reliability estimation methods, marginal reliability coefficient was determined to be .77 according to IRT. In the test-retest applications performed at 20-day intervals, the stability coefficient was found to be.81.